PSYCHO-SOCIAL CAUSAL FACTORS OF TEACHERS’ WORK LIFE QUALITY - Pomchiangohang, Noppharat; Pomchiangohang, Noppharat; Meekun, Kosol (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The objectives of this research were to study 1) relationship between the psychological factor and the social situation factor of teachers’ work life quality, 2) predictive volume of teachers’ work life quality by using psychological variables and social situation variables, and 3) search groups of teachers that should be developed first on their quality of work life and factors that should be promoted. The sample group of this research comprised of 135 teachers in primary school, Dusit District Office in Bangkok, in the Academic Year 2022. Instrument of this research were 7 summated rating scales with r item-total correlation .315 to .833, reliability .786 to .898. The statistics for data analysis were basic statistics, and inferential statistics namely: t-test and multiple regression. Research finding were: 1) relationship between psychological factors, social situation factors and teachers’ work life quality were moderately high (r = .428 to .667) 2) psychological factor and social situation factors could predicted teachers’ work life quality by 43.00% and 44.10% respectively, psychological factor collaborated with social situation factor could explained teachers’ work life quality by 57.40 % and 3) teachers who should be developed first on the quality of work life were male teachers and assistant teachers combined with K1 teachers, the factors should be promoted were the organizational atmosphere, readiness for work, Innovative adoption, and mental health.